VD_FINDINFO HC / 2013 / 35 vom 16. Januar 2013 - VD Tribunal cantonal (2013)
PROTECTION DE L'UNION CONJUGALE, SÉPARATION DE BIENS | 176 al. 1 ch. 3 CC, 176 CC, 308 al. 1 let. b CPC (CH), 308 CPC (CH), 312 al. 1 CPC (CH)